The analysis of the solution of match situation 1 v 1 within the attacking phase in soccer - Kovac, V. (Acta Universitatis Matthiae Belii, Physical Education and Sport, 2013)
In our study we tried to watch a solution of match situation 1-1 in offensive phase of the game. Four soccer players participated in this study (all of them were offensive central midfielders), who were watched during particular matches from EURO 2004 in Portugal. The aim of the study was watching them in followed matches and wrote down all kinds of their solution of match situation 1-1 in offensive part of game. After the research it is reasonable to conclude, that offensive midfielders from EURO 2004 mostly preferred a "the kick trick feint" and "the dummy step feint". As the least common used feint was "the nutmeg move feint". The feint realized with the most success was "the foot on the ball trick" and "the dummy step feint". So it is presumable that within the match microsituation 1 v 1 in the offensive part of the game realized by offensive midfielders "the kick trick feint" will be the most prefered . It is happening becouse of the narrow size of the playing area mostly prefered nowadays by teams within a defensive part of game.